SIG Berbasis Web untuk SDG 14 di ASEAN Menggunakan Metode Extreme Programming - Salsabila, Adinda; Hadi, Setiawan; Suryana, Ino (JITSI : Jurnal Ilmiah Teknologi Sistem Informasi, 2025)
Sustainable Development Goal 14 focus on sustainable development in the marine sector by emphasizing key focus areas such as Marine Protected Areas, Total Fisheries Production, Aquaculture Production, and Capture Fisheries Production. The ASEAN region, with its rich marine biodiversity, faces serious threats, including overfishing. However, no interactive platform is currently available to comprehensively visualize relevant data. This research aims to develop a web-based Geographic Information System (GIS) to visualize SDG 14 data in ASEAN using the Extreme Programming approach. This study employs the Research and Development (R&D) method with an Extreme Programming approach, allowing iterative software development. Primary data, including marine protected areas and fisheries production, were obtained from reliable sources such as the World Bank and visualized using Leaflet.js with geospatial data in GeoJSON format. System testing was conducted through Black Box Testing and the System Usability Scale (SUS), integrated into a survey form completed by 32 respondents to assess the system's accuracy and ease of access. The test results indicate that the system can provide accurate and easily accessible information, with a Black Box Testing score of 99.79%. Additionally, the Mean Absolute Percentage Error (MAPE) calculation resulted in a value of 0.21%, demonstrating a very high accuracy in system predictions. The SUS score reached 94.03%, reflecting a very high level of user satisfaction. This system successfully meets the need for SDG 14 data visualization, supports decision-making, and raises public awareness of marine ecosystem conservation in ASEAN.